Reduced diversity in the early fecal microbiota of infants with atopic eczema - Wang, Mei; Karlsson, Caroline; Olsson, Crister; Adlerberth, Ingegerd; Wold, Agnes E.; Strachan, David P.; Martricardi, Paolo M.; Åberg, Nils; Perkin, Michael R.; Tripodi, Salvatore; Coates, Anthony R.; Hesselmar, Bill; et al. (Journal of allergy and clinical immunology, 2008)
It might be that early intestinal colonization by bacteria in westernized infants fails to give rise to sufficient immune stimulation to support maturation of regulatory immune mechanisms. The purpose of the present study was to characterize the very early infantile microbiota by using a culture-independent approach and to relate the colonization pattern to development of atopic eczema in the first 18 months of life. Fecal samples were collected from 35 infants at 1 week of age. Twenty infants were healthy, and 15 infants were given diagnoses of atopic eczema at the age of 18 months. The fecal microbiota of the infants was compared by means of terminal restriction fragment length polymorphism (T-RFLP) and temporal temperature gradient gel electrophoresis (TTGE) analysis of amplified 16S rRNA genes. By means of T-RFLP analysis, the median number of peaks, Shannon-Wiener index, and Simpson index of diversity were significantly less for infants with atopic eczema than for infants remaining healthy in the whole group and for the Swedish infants when AluI was used for digestion. The same was found when TTGE patterns were compared. In addition, TTGE analysis showed significantly less bands and lower diversity indices for the British atopic infants compared with those of the control subjects. There is a reduced diversity in the early fecal microbiota of infants with atopic eczema during the first 18 months of life.